Incident with multiple victims: Report of realistic simulation in a public university - Rodrigues, Clícia Burle; Nascimento, Lucas de Andrade; Silva, Maria Dolores Lima da; Kameo, Simone Yuriko (Seven Editora, 2023)
Teaching through simulation allows training in real conditions, with actors and partners, in an interactive way in a controlled environment. The realistic simulation provides the student with contact with the practice for the development of capacities and skills, bringing him closer to reality. DOI:https://doi.org/10.56238/globalhealthprespesc-063